Optimalisasi Peran Lembaga Dakwah Kampus dalam Meningkatkan Kecerdasan Emosional Mahasiswa PAI FITK UINSU Medan - Mawarni, Widya Tri; Arlina, Arlina (Kamaya: Jurnal Ilmu Agama, 2025)
This study aims to analyze the optimization of the role of the Campus Da'wah Institute (LDK) in improving the emotional intelligence of students of the Islamic Religious Education Study Program (PAI), Faculty of Tarbiyah and Teacher Training (FITK), State Islamic University of North Sumatra (UINSU) Medan. Using a qualitative approach of the phenomenological type, this study seeks to identify aspects of emotional intelligence that develop through student participation in LDK organizations. Data was collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawn. To ensure the validity of the data, the researcher applied triangulation and prolonged engagement techniques. The results of the study show that LDK has a significant role in improving students' emotional intelligence through five aspects, namely: enhancing self-awareness, enhancing self-control, building self-motivation, enhancing empathy, and improving social skills.